2015
DOI: 10.1038/ncomms8868
|View full text |Cite|
|
Sign up to set email alerts
|

A molecular propeller effect for chiral separation and analysis

Abstract: Enantiomers share nearly identical physical properties but have different chiral geometries, making their identification and separation difficult. Here we show that when exposed to a rotating electric field, the left- and right-handed chiral molecules rotate with the field and act as microscopic propellers; moreover, owing to their opposite handedness, they propel along the axis of field rotation in opposite directions. We introduce a new molecular parameter called hydrodynamic chirality to characterize the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Clemens and coworkers 27 nevertheless did attempt to perform chiral separation at the molecular scale. To this end, they surrounded a capillary tubing with four electrodes (see Fig.…”
Section: At the Molecular Scalementioning
confidence: 99%
“…Clemens and coworkers 27 nevertheless did attempt to perform chiral separation at the molecular scale. To this end, they surrounded a capillary tubing with four electrodes (see Fig.…”
Section: At the Molecular Scalementioning
confidence: 99%
“…[22,23] It has been shown that the bi-chiral plasmonic arrays can possess complexly chiroptical responses once the strong coupling occurs between the chiral centers, for example by changing their relative distance to tune their coupling. [22] Inspired by the emerging propeller chirality in molecular systems, [24][25][26][27][28][29] here we report a novel scheme to construct the bi-chiral plasmonic arrays and realize the strong coupling between the chiral centers to achieve the phase enabled circular dichroism reversal. As illustrated in Figure 1a, the proposed RH propeller metamolecules consist of three twisted blades that are connected by a chiral center R. Such an artificial metamolecule mimics well the configuration of propellertype chemical molecules, in which the molecular blades were unidirectionally twisted with respect to the central group.…”
Section: Phase Enabled Circular Dichroism Reversal In Twisted Bi-chiral Propeller Metamolecule Arraysmentioning
confidence: 99%
“…In Ref. [13], it was shown that when exposed to a rotating electric field (at the frequency of 900 kHz), the left-and right-handed chiral molecules rotate with the field and act as microscopic propellers. Owing to their opposite handedness, they propel along the axis of field rotation in opposite directions.…”
mentioning
confidence: 99%